Association of Pre-miR-146a rs2910164 Polymorphism with Papillary Thyroid Cancer - Xin Zhang; Yulu Gu; Xiaoli Liu; Yaqin Yu; Jieping Shi; Qiong Yu; Hui Sun; Joseph Sam Kanu; Siyan Zhan; Yawen Liu (International Journal of Endocrinology)
The incidence rate of papillary thyroid cancer (PTC) has increased over the past decades, but the pathogenesis remains unclear. rs2910164, located in pre-miR-146a, has been studied in PTCs with different ethnicity, but the results were inconsistent. Here we evaluate the association between rs2910164 polymorphism and PTC and investigate the effect of this polymorphism on patients’ clinicopathological characteristics. 1238 PTC patients and 1275 controls, all Han population, from Northern China, were included in our study. rs2910164 was genotyped using Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS). Analysis of inheritance model was performed using the SNPStats program. Strength of association was assessed by odds ratio (OR) and 95% confidence interval (CI). Overall, no statistical difference in rs2910164 genotype distribution and allelic frequencies between cases and controls was found, and patients with different genotypes had similar clinicopathological characteristics in terms of stage, location, concurrent of benign thyroid tumor, and thyroiditis, while, as the number of G alleles increased, proportion of patients aged ≥45 years and those without metastasis increased (Ptrend<0.001 and Ptrend=0.003, resp.). However, no association remained significant after Bonferroni correction under any model of inheritance. Our results suggest no association between rs2910164 polymorphism with PTC and patients’ clinicopathological characteristics.